OPTIMALISASI USAHATANI SAYURAN CABAI, TOMAT PADA MUSIM GADU DENGAN PENDEKATAN LINEAR PROGRAMMING DI DESA MAOUTONG KECAMATAN TILONGKABILA BONE BOLANGO: Optimization of Cabai Vegetable, Tomato Vegetables In The Gadu Season With Linear Programming Approach In Maoutong Village, Tilongkabila District Bone Bolango - Zainal Abidin; Siska Karim (Jurnal Agribis, 2019)
The purpose of this optimization is expected to be able to display an output that provides important information for farmers regarding the actual and optimal conditions of chili, tomato farming in the gadu season in Moutong Village, Tilongkabila District, Kabupaen Bone Bolango. The sampling method used in this study was purposive sampling. The number of respondents used in this study were 25 vegetable farmers in Moutong Village. The amount is also taken with consideration of the constraints of time, energy, and cost. The results showed that vegetable farming in the gadu season in Moutong Village, Tilongkabila District, Bone Bolango Regency, the use of land resources, labor and capital available at the research location, the average capital of vegetable farming was not used up. In the actual farming conditions, respondents' income is 201,600,000.